2020
DOI: 10.1002/fsh.10389
|View full text |Cite
|
Sign up to set email alerts
|

Per‐ and Polyfluoroalkyl Substances (PFAS): Anglers May Be Exposed to Harmful Chemicals in Their Catch

Abstract: In this review, we focus on per‐ and polyfluoroalkyl substances (PFAS), synthetic compounds used for a variety of applications, including firefighting foam and manufacturing. Recently, researchers have linked human exposure to PFAS to negative health effects. Hundreds of communities are affected by PFAS contamination, which has raised awareness about the toxicity of these chemicals. Most work has focused on characterizing dangers to humans, and the effects of PFAS on the environment are under‐studied. PFAS con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Over the past few years, various research has revealed the growing dangers associated with PFAS on the body, encompassing concerns such as cancer, thyroid disorders, developmental anomalies in children, and immune system dysfunction [10,11]. It is well known that the carcinogenic potential of PFAS has been associated with various cancers due to the PFAS-induced oxidative stress that plays a role in cellular damage and DNA mutations, contributing to cancer development [12,13]. Furthermore, studies have shown that by interfering with hormonal regulation systems and suppressing immune system function, PFAS can lead to disorders like hypothyroidism, developmental anomalies, such as stunted growth and delayed cognitive development in children, and neurotoxic effects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, various research has revealed the growing dangers associated with PFAS on the body, encompassing concerns such as cancer, thyroid disorders, developmental anomalies in children, and immune system dysfunction [10,11]. It is well known that the carcinogenic potential of PFAS has been associated with various cancers due to the PFAS-induced oxidative stress that plays a role in cellular damage and DNA mutations, contributing to cancer development [12,13]. Furthermore, studies have shown that by interfering with hormonal regulation systems and suppressing immune system function, PFAS can lead to disorders like hypothyroidism, developmental anomalies, such as stunted growth and delayed cognitive development in children, and neurotoxic effects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary exposure to PFAS, Hg, and other contaminants through harvest and consumption of wild foods is of concern (Denys et al, 2014; Fraley et al, 2020), and has led to federal and local testing of wildlife and fish tissues near contaminated areas (see Alaska Department of Environmental Conservation, 2019; New Jersey Department of Environmental Protection, 2018). The results from testing have led to issuance of consumption advisories, moratoriums on fish harvest, and hunting and fishing closures in some instances (Alaska Department of Fish and Game, 2019; Minnesota Department of Health, 2018).…”
Section: Introductionmentioning
confidence: 99%